Accompaniment, Silence, or Tolerance of the Islamic Legislator with the Conduct of the Wise - Mahdi Montazerqaem (پژوهش‌نامه حقوق اسلامی)
‌ ∴ Introduction ∴ ‌This paper addresses the nuanced relationship between Islamic jurisprudence (Fiqh) and the evolving conduct of society, specifically within the context of the wise (ʿuqalāʾ). The debate over the origin of moral values—whether they are inherently recognized by reason, divinely assigned, or conventionally accepted by society—has long occupied the attention of Islamic scholars, particularly within the Imamiyyah (Shia) tradition. This paper explores the Legislator's stance toward the conduct of the wise, focusing on how these conducts interact with the principles of Sharia, particularly in the realm of transactions.     The three primary perspectives on the origin of moral values in Islam are Ash'arism, Mu'tazilism, and a particular viewpoint within the Shia (Imamiyyah). Each of these schools of thought offers a distinct interpretation of the relationship between divine command and human reason in determining the moral value of actions. This paper, however, zeroes in on the third perspective within the Imamiyyah tradition, which posits that the moral value of actions like justice and injustice is recognized by the wise and is a product of societal conventions rather than an inherent or divinely assigned characteristic.     The primary aim of this paper is to examine the Legislator's (Allah's) stance on the conduct of the wise in a contemporary context, especially as modern conduct have developed in ways that sometimes conflict with traditional Islamic legal teachings. By exploring the concepts of accompaniment, silence, or tolerance by the Legislator, the paper seeks to clarify how Islamic law can remain relevant and just in the face of evolving societal norms and conduct.     The implications of this discussion are profound, particularly in light of the challenges posed by modernity and the globalized world. The paper delves into the ways in which Islamic jurisprudence can accommodate or resist these changes without undermining the fundamental principles of Sharia. This exploration is crucial for contemporary Islamic scholars, who must navigate the tension between upholding traditional legal teachings and addressing the practical needs of a modern Muslim society.‌ ∴ Research Question ∴ ‌The central research question of this paper is: How does the Legislator's stance—whether of accompaniment, silence, or tolerance—toward the conduct of the wise impact the application of Sharia in the context of modern societal practices, particularly in the domain of transactions?     This question is pivotal because it addresses the broader issue of how Islamic law interacts with evolving societal norms. As conduct change and develop over time, they often present challenges to established legal and religious frameworks. The research seeks to determine whether the Legislator's stance toward these conducts allows for flexibility within Sharia or whether it necessitates a more rigid adherence to traditional interpretations, even at the cost of causing harm, hardship, or corruption within society.‌ ∴ Research Hypothesis ∴ ‌The hypothesis of the research is that the Legislator's opposition to the conduct of the wise weakens the efficacy and relevance of Sharia, imposes unnecessary hardships on the Muslim community, and undermines societal interests. Conversely, by accompanying, remaining silent, or showing tolerance toward these conducts, the Legislator preserves the integrity of Islamic law while ensuring that it remains aligned with the practical needs and moral intuitions of society.     This hypothesis challenges the traditional notion that Islamic law is static and unchanging. Instead, it suggests that the Legislator's approach to conduct is dynamic and context-dependent, allowing for a more flexible application of Sharia that can accommodate the changing moral landscape of society. The hypothesis also implies that a rigid, unyielding application of Sharia that ignores the conduct of the wise may lead to outcomes that are contrary to the objectives of Islamic law, such as justice, mercy, and the prevention of harm.‌ ∴ Methodology & Framework, if Applicable ∴ ‌The research is conducted using a doctrinal approach, which involves a detailed analysis of primary and secondary Islamic legal sources, including the Quran, Hadith, and the writings of classical and contemporary jurists. This approach is supplemented by a critical examination of the conduct of the wise and their evolution over time, particularly in response to changing social, economic, and political conditions.     The framework for this analysis is built around three key concepts: accompaniment, silence, and tolerance. Each of these concepts represents a different way in which the Legislator might interact with the conduct of the wise:     Accompaniment refers to instances where the Legislator actively endorses and supports a particular custom, aligning it with the primary teachings of Sharia.     Silence refers to cases where the Legislator neither endorses nor opposes a custom, thereby allowing it to persist without explicit approval or rejection.     Tolerance refers to situations where the Legislator does not agree with a custom but refrains from opposing it due to the potential harm, hardship, or corruption that might result from such opposition.     The research also employs a comparative analysis to explore how these concepts have been applied in different historical and geographical contexts. This includes examining the ways in which Islamic jurists have historically dealt with conduct that conflicted with Sharia, as well as how contemporary jurists are addressing similar issues in the modern world. By doing so, the research seeks to identify patterns and principles that can guide the application of Sharia in relation to the conduct of the wise in today's society.     The paper's approach is both analytical and normative, aiming not only to describe how Islamic law has historically interacted with societal conduct but also to offer normative guidelines for how it should do so in the future.‌ ∴ Results & Discussion ∴ ‌The exploration of the Islamic legislator's stance towards the conduct of the wise (Sīrah al-ʿUqalāʾ) reveals significant implications for contemporary Islamic jurisprudence. The results of this research indicate that Islamic legal rulings are not inherently opposed to the conduct of the wise, but rather, they are flexible and responsive to societal changes through a process of alignment, silence, or tolerance. The key findings can be summarized as follows:     Alignment with Conduct: The research confirms that in many instances, the Legislator aligns with the conduct of the wise, particularly those that resonate with the fundamental principles and objectives of Sharia. This alignment suggests that Islamic law is not static but can evolve to accommodate societal changes, provided these changes do not conflict with the core values of Islam. This perspective supports the idea conduct promote justice, fairness, and social welfare are likely to be endorsed by the Legislator.     Silence toward New Conduct: Another significant finding is the Legislator's silence in response to new conduct. This silence does not imply indifference but rather a deliberate choice to allow this conduct to persist without direct interference. The silence of the Legislator can be interpreted as a form of tacit approval, particularly in cases where the new conduct do not directly contradict Islamic principles but rather exist in areas not explicitly addressed by primary legal evidence. This finding emphasizes the importance of considering silence as a form of legal reasoning within Islamic jurisprudence.     Tolerance of Conflicting Conduct: The most complex and perhaps controversial finding is the Legislator's tolerance toward conduct that, on the surface, appear to contradict primary religious evidence. This tolerance is understood through the concept of secondary legal evidence, which can validate conduct by acting as negative evidence that nullifies conflicting rulings. The research shows that the Legislator’s tolerance is a pragmatic approach to prevent harm, hardship, or societal disruption, which could result from rigidly applying primary legal rulings without consideration of the conduct of the wise. This tolerance underscores the adaptability and resilience of Islamic law in the face of changing societal norms.     Role of Secondary Legal Evidence: The discussion highlights the critical role of secondary legal evidence in reconciling apparent conflicts between Islamic law and societal conduct. Secondary evidence serves as a means to prioritize the objectives of Sharia, such as preventing harm and promoting societal welfare, over strict adherence to primary rulings that may not be applicable in modern contexts. This finding suggests that secondary legal evidence can limit or even override primary evidence when it comes to conduct that have gained widespread acceptance among the wise.     Practical Application: In practice, the research concludes that Islamic legal rulings must be interpreted and applied in a manner that considers the conduct of the wise as a significant factor. This approach ensures that the law remains relevant and effective in addressing contemporary issues. The discussion emphasizes that any ruling that conflicts with established conduct of the wise is likely to be viewed as inconsistent with the Legislator's intent and, therefore, should not be enforced. This pragmatic approach to Islamic law highlights the need for jurists to be attuned to societal changes and to interpret Sharia in a way that aligns with the evolving moral and social landscape.     Jurists’ Role in Shaping Conduct: Finally, the research touches on the proactive role that religious scholars and jurists can play in gradually shaping the conduct of the wise to better align with the principles and objectives of Sharia. This finding points to a dynamic interaction between Islamic law and society, where scholars are not merely passive observers but active participants in guiding societal norms in a direction that reflects Islamic values.‌ ∴ Conclusion ∴ ‌The conclusion of this research underscores the flexibility and adaptability of Islamic law in relation to the conduct of the wise. The analysis reveals that the Islamic Legislator does not inherently oppose societal conduct but instead adopts a nuanced approach that includes alignment, silence, or tolerance depending on the nature of the custom and its impact on society.     The key conclusion is that no Islamic legal ruling should be enacted or enforced if it directly contradicts the established conduct of the wise, particularly when such conduct is supported by secondary legal evidence. This perspective suggests that the conduct of the wise play a crucial role in shaping the practical application of Sharia, serving as a form of negative evidence that can nullify conflicting primary rulings. As a result, the Legislator’s tolerance toward such conduct can be seen as a means of safeguarding the religion and the community from harm, hardship, and social disruption.     Moreover, the research concludes that religious scholars and jurists must recognize the importance of conduct in the legal framework and work to harmonize Islamic law with societal practices. This does not mean compromising on core Islamic principles but rather ensuring that the application of these principles is contextually relevant and socially just. The research advocates for a jurisprudence that is both rooted in traditional Islamic teachings and responsive to the needs of contemporary society.     In conclusion, the paper asserts that the flexibility inherent in Islamic jurisprudence allows it to remain a living tradition that can effectively address the challenges posed by modernity. The conduct of the wise are not merely to be tolerated; they are to be understood as integral to the continued relevance and applicability of Sharia in the modern world. By prioritizing the objectives of Sharia—such as justice, mercy, and the prevention of harm—over rigid adherence to primary legal rulings, Islamic law can continue to serve as a source of guidance and wisdom for Muslim communities across the globe.